Microbiological quality of sorbetes (Dirty ice cream) produced from three selected sources in San Jose, Antique - Ortiaga, Clarissa C.
Sorbetes collected from the three selected sources, identified as Sources A, B, and C, in San Jose, Antique were subjected to microbiological analyses namely, APC, yeast and molds count, psychotropic count, MPN of coliforms and faecal coliforms and detection of E. coli, Salmonella and S. aureus.